2019
DOI: 10.1177/0363546519886548
|View full text |Cite
|
Sign up to set email alerts
|

Minimum 10-Year Clinical and Radiological Outcomes of a Randomized Controlled Trial Evaluating 2 Different Approaches to Full Weightbearing After Matrix-Induced Autologous Chondrocyte Implantation

Abstract: Background: Longer term outcomes after matrix-induced autologous chondrocyte implantation (MACI) are lacking, while early postoperative weightbearing (WB) management has traditionally been conservative. Purpose: To investigate the longer term clinical and radiological outcomes after an 8-week (vs 12-week) WB protocol after MACI. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A randomized study design allocated 70 patients to an 8- (n = 34) or 12-week (n = 36) approach to full WB afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(107 citation statements)
references
References 49 publications
5
96
2
4
Order By: Relevance
“…The MACI procedure is a 2-stage surgical technique and has been described previously. 8,13 Via an initial arthroscopic procedure a sample of articular cartilage was harvested and chondrocytes subsequently isolated, cultured (Genzyme), and seeded onto a type I/III collagen membrane (ACI-Maix; Matricel GmbH) ex vivo over a 6- to 8-week period. In a second surgical procedure via an open arthrotomy, the cartilage defect was prepared by removing all damaged cartilage down to the subchondral bone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MACI procedure is a 2-stage surgical technique and has been described previously. 8,13 Via an initial arthroscopic procedure a sample of articular cartilage was harvested and chondrocytes subsequently isolated, cultured (Genzyme), and seeded onto a type I/III collagen membrane (ACI-Maix; Matricel GmbH) ex vivo over a 6- to 8-week period. In a second surgical procedure via an open arthrotomy, the cartilage defect was prepared by removing all damaged cartilage down to the subchondral bone.…”
Section: Methodsmentioning
confidence: 99%
“…5,6,10,11,17,35 However, only limited studies are available reporting outcomes for third-generation ACI techniques beyond 10 years, with these generally including smaller patient cohorts and/or lacking postoperative MRI evaluation. 1,8,18,26 Published third-generation studies by Aldrian et al, 1 Gille et al, 18 and Niethammer et al 26 reported outcomes at ≥10 years in 16, 18, and 30 patients, respectively. The largest 10-year cohort published recently was in 60 patients, although it was isolated to grafts in the tibiofemoral joint (medial and lateral femoral condyles [MFCs and LFCs]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrin glue is currently readily available for human applications and has a strong track record of being successfully applied clinically to support cell-based therapies within the human knee joint. 8,12,13 Fibrin glue is the recommended product used to facilitate matrix-induced autologous chondrocyte implantation, a cartilage restoration therapy approved by the FDA for use in humans. In addition, the ability to use human cells rather than nonhuman cells for efficacy experiments in this porcine model increases the translational potential of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…In studies comparing WB progression after MACI, patients who progressed to weight bearing as tolerated (WBAT) by 6 to 8 weeks as compared with 10 to 12 weeks were reported to have improved clinical and functional outcomes without an increase in failure rate. 45,46 However, ACI should progress WB activities more cautiously than MACI, with partial (one-fourths body weight) WB initiated at 2 to 4 weeks and gradually increased to WBAT by 8 to 12 weeks. 39,42,43 The use of an unloader brace may be indicated for larger tibiofemoral lesions, and can aid in the reduction of compressive forces on treated sites during WB activities.…”
Section: Phase I: Proliferation (Weeks 0-6)mentioning
confidence: 99%